2006
DOI: 10.1111/j.1468-3083.2006.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

Kaposiform hemangioendothelioma in an adult with an unusual presentation

Abstract: detectable by PCR in PBMC. If such is indicative of active infection, 30% of healthy individuals would be having active HHV-7 infection at any one time point.In summary, we compliment Vág et al. in having reported a high-quality study with a novel approach, but are unconvinced that their results provide conclusive evidence of recent primary HHV-7 infection in young adults with PR. References1 Vág T, Sonkoly E, Kárpáti S, Kemény B, Ongrádi J. Avidity of antibodies to human herpesvirus 7 suggests primary infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…It can be differentiated from tufted angioma by deeper and infiltrative growth pattern. Although common in childhood, KMP has not been reported in adults 4 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It can be differentiated from tufted angioma by deeper and infiltrative growth pattern. Although common in childhood, KMP has not been reported in adults 4 …”
Section: Discussionmentioning
confidence: 97%
“…Based on the clinicopathological findings, other differential diagnoses that need to be ruled out include kaposiform hemangioendothelioma, kaposi sarcoma and eccrine angiomatous hamartoma. Kaposiform hemangioendothelioma is a locally aggressive vascular tumor that typically occurs in infants and children and is rarely encountered in adults 4,5 . It manifests as ill‐defined violaceous ulcerated plaques on the extremities and trunk.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes and all, reviewed all the articles talking about HEK and KMP and published in Pub Med, from April 1993 to July 2007, he found that only 20 adults were recorded (2,6,7,8,9,10,11,12,13) Since then, some other cases, about twelve, have been described all over the world. (14,15,16,17,18,19,20,21,22) The KHE has got two clinical presentations : cutaneous and visceral.…”
Section: Discussion:-mentioning
confidence: 99%
“…Common tumor locations included the extremities (9 cases, 39.1%), the torso (7 cases, 30.4%), and the cervicofacial region (5 cases, 21.7%). In adults, KHE usually involves dermal and subcutaneous tissues (65.2%) [1,2,3,4,5,6,7,8,9,11,13,14,17]. None of the 23 cases showed evidence of KMS, and just 2 patients had lymphangiomatosis (8.7%) [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…KHE typically occurs during infancy and in the first decade of life. Although KHE may also develop in adults, only approximately 20 adult KHE patients have been reported (table 1) [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]; most of them were not associated with KMS [6]. KHE rarely originates from bone without accompanying cutaneous changes.…”
Section: Introductionmentioning
confidence: 99%